Scientific Literacy and Health Behavior: A Study on Knowledge and Attitudes Towards IUD Contraception Among Reproductive-Age Women in Muara Enim District - Rahmadyanti; Asterianah; Isna Yunita; Kiki Amelia; Lisna Anggraini; Meila Puspita Sari; Yuli Awaliah; Yulyana Jambi (Jurnal Penelitian Pendidikan IPA, 2025)
The use of Intrauterine Devices (IUDs) as a method of long-term contraception remains low in several regions of Indonesia, including Muara Enim District. Understanding the determinants that influence women's interest in using IUDs is essential to improve reproductive health programs and reduce unmet contraceptive needs. This study aims to identify and analyze the determinants that influence the interest and decision to use IUD contraception among women of reproductive age in Muara Enim District, South Sumatera. A cross-sectional design was used involving 200 women of reproductive age (15–49 years), selected through stratified random sampling. Data were collected using structured questionnaires and analyzed using multivariate logistic regression to determine the most influential factors. The study found that key determinants influencing IUD use included level of knowledge about IUDs (OR = 2.35, 95% CI: 1.42–3.89), spousal support (OR = 3.10, 95% CI: 1.75–5.49), perceived side effects (OR = 0.48, 95% CI: 0.27–0.86), and access to family planning services (OR = 2.01, 95% CI: 1.10–3.66). Educational level and previous counseling experiences were also found to be associated with higher interest in using IUDs. Interest in using IUD contraception is influenced by a combination of knowledge, social support, perception of risk, and service accessibility. Public health interventions should prioritize reproductive health education, spousal involvement, and expansion of accessible and reliable family planning services to increase IUD adoption in rural districts.